2018
DOI: 10.3390/environments5020031
|View full text |Cite
|
Sign up to set email alerts
|

Deriving a Benefit Transfer Function for Threatened and Endangered Species in Interaction with Their Level of Charisma

Abstract: Biodiversity and species conservation are among the most urgent global issues. Both are under serious threat because of human intrusion and as a result, it is likely that present and future projects will affect threatened and endangered species. Thus, it is important to account for these impacts when evaluating and conducting cost and benefit analyses of projects. Due to their public good character and non-tradability, the total economic value of threatened and endangered species cannot be reflected by a marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
1
1
0
Order By: Relevance
“…Of the taxa sampled, the two most intensively researched taxonomic groups for both data sets were bony fishes (39% PCB ST and 42% of the standardized set of seven PCBs) and mammals (32% and 25% of PCB ST and the set of seven, respectively), while amphibians, echinoderms, arachnids, and sea squirts have been relatively understudied overall (Figure C). This skew in sampling effort likely reflects the economic value and human health concerns associated with commercial and recreational fisheries, the propensity of environmental risk assessment studies to select indicator species representative of environmental health, and the economic or charismatic value of large-bodied mammals, including dolphins, whales, and seals. The relatively low representation of primary producers, however, is due in part to our particular focus on studies reporting PCB concentrations in lipid-normalized units of measurement, as plant PCB values are more commonly reported in relation to a sample’s wet weight. In general, our syntheses indicate that far more research on lower trophic levels and on a broader range of taxa is needed to gain holistic understanding of the key pathways through which PCBs are integrated into and accumulate within food webs.…”
Section: Results and Discussionsupporting
confidence: 69%
“…Of the taxa sampled, the two most intensively researched taxonomic groups for both data sets were bony fishes (39% PCB ST and 42% of the standardized set of seven PCBs) and mammals (32% and 25% of PCB ST and the set of seven, respectively), while amphibians, echinoderms, arachnids, and sea squirts have been relatively understudied overall (Figure C). This skew in sampling effort likely reflects the economic value and human health concerns associated with commercial and recreational fisheries, the propensity of environmental risk assessment studies to select indicator species representative of environmental health, and the economic or charismatic value of large-bodied mammals, including dolphins, whales, and seals. The relatively low representation of primary producers, however, is due in part to our particular focus on studies reporting PCB concentrations in lipid-normalized units of measurement, as plant PCB values are more commonly reported in relation to a sample’s wet weight. In general, our syntheses indicate that far more research on lower trophic levels and on a broader range of taxa is needed to gain holistic understanding of the key pathways through which PCBs are integrated into and accumulate within food webs.…”
Section: Results and Discussionsupporting
confidence: 69%
“…Meanwhile, a previous study showed that the endangered status of a species did not attract the attention of people in a conservation program, but rather, the charisma of the species was a factor due to which the interest of people and activeness in participating in the program were high [32]. Another study showed that the combination of threat to a species and its charisma has positive effects on the willingness to pay for an endangered species [33]. However, our results show that a lack of charisma is not the only reason for the low interest in endangered species.…”
Section: Discussionmentioning
confidence: 99%
“…Preferences for environmental conservation are expected to differ across individuals and have been observed to vary with multiple determining factors including the (perceived) scarcity and proximity of the resource, and the dependence on the resource of the individual (Wallmo and Lew, 2012;Amuakwa-Mensah et al, 2018). The scarcity of a resource can draw the attention of stakeholders and induce individuals to manage scarce resources more carefully (Mullainathan and Sha r, 2013; Muthulingam et al, 2021;Shah et al, 2015).…”
Section: Mainmentioning
confidence: 99%